2019
DOI: 10.1519/jsc.0000000000002001
|View full text |Cite
|
Sign up to set email alerts
|

Endurance Running Training Individually Guided by HRV in Untrained Women

Abstract: The aim of this study was to analyze the effects of HRV-guided training compared to a standardized prescription on i) time to complete 5-km running performance (t5km), ii) peak treadmill running speed (Vpeak) and its time limit (tlim at Vpeak), and iii) autonomic cardiac modulation (i.e., parasympathetic activity and recovery) in untrained women. Additionally, we correlated changes in t5km with changes in Vpeak, tlim at Vpeak and autonomic cardiac modulation. Thirty-six untrained women were divided into a HRV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(96 citation statements)
references
References 31 publications
7
89
0
Order By: Relevance
“…Consequently, the percentage of time below VT1 was higher (but not significantly) in HRV-G while time expended upper VT2 remained similar between groups. The distribution in HRV-G is in accordance with the report by Da Silva et al 32 which found a lower proportion of moderate intensity for the HRV guided training group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consequently, the percentage of time below VT1 was higher (but not significantly) in HRV-G while time expended upper VT2 remained similar between groups. The distribution in HRV-G is in accordance with the report by Da Silva et al 32 which found a lower proportion of moderate intensity for the HRV guided training group.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, HRV-G lead to substantial greater increase in this variable with higher magnitude of change. The finding mirrors those of the previous studies 5, 32 that have examined the effect of a day-to-day training prescription based on HRV compared to a traditional training prescription. In this case, power output during 40TT was between WVT1 and WVT2 (Table 3), while the percentage of time expended at moderate intensity (between VT1 and VT2) was significantly lower the in HRV-G group.…”
Section: Regarding These Differences Training Prescription Based On supporting
confidence: 87%
“…Thus, different studies found that grater vagal modulations are related to better training response, adaptation, and recovery in both low-and high-intensity training [69,72]. Moreover, several studies showed how training-load guided by HRV monitoring was more efficient than traditional periodization for training adaptations in both males [70] and females [73] when identifying greater-stress days, thereby reducing the runners' potential for adaptation and requiring a lowered training load. While some HR monitors offer this monitoring tool, this approach is currently easier to implement with different easy-to-use apps (e.g., HRV4training; [74]), which integrate HRV measures with other load and psychometric measures.…”
Section: Training Monitoringmentioning
confidence: 99%
“…Furthermore, day-to-day fluctuations might be interpreted as (physiological) signal , and changes being related to training load, stress, and fatigue (Stanley et al, 2013 ). In line with the latter assumption, several attempts have been made to guide training programs based on daily (resting) HRV as a marker of (cardiovascular) recovery, resulting in either larger adaptations or more efficient training compared to conventional predefined training programs (Kiviniemi et al, 2007 , 2010 ; Vesterinen et al, 2016 ; da Silva et al, 2017 ; Nuuttila et al, 2017 ). However, it must be considered that HRV-guided training programs have always been exclusively based on endurance training and were subject to certain restrictions and training principles (for example, a maximum of two successive high-intensity training days).…”
Section: Hr Monitoring In Athletesmentioning
confidence: 99%